IstikhdÄm Namudhaj al-Maâ€™raá¸ al-MÄshi (Gallery Walk) li Taâ€™lÄ«m al- TarÄkib fÄ« al-Madrasah al-ThÄnawiyyah al-IslÄmiyyah al-á¸¤ukÅ«miyyah 3 Agam - Helmi, Helmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The problem in tarkib learning (structure) is the lack of student motivation and interest in learning because teachers use traditional learning models that center on the teacher. The purpose of this study was to determine how tarkib learning with the Gallery Walk model, its effectiveness, and how students respond to tarkib learning using the Gallery Walk model at MTsN 3 Agam. Researchers use experimental methods with True Experimental Design. The research instruments were a post-test test and a questionnaire. The population of this study was all seventh-grade students of MTsN 3 Agam in the 2022-2023 school year while the research sampling technique was Simple Random Sampling. Research results: (1) Students share thoughts and discussions about tarkib, pour it on large paper, and then stick it on the wall of the classroom. Then the group goes around while the speaker stays in the group to explain the results of the group to visitors who continue to return to their respective groups and explain it to the speaker of the group. (2) The Sig. (2-tailed) value of 0.032 is smaller than 0.05 and the results of the t-count value (2.190) and t-table (1.998). The t-count is greater than the t-table, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. (3) Analysis of student responses showed (a) 85.31% of students were interested in the Gallery Walk model (very positive response) (b) 86% of students stated that the Gallery Walk model was useful (very positive response) and (c) 86.25% of students' desire to use the Gallery Walk model in other lessons.